THE QUALITY OF E-KTP SERVICE IN CIBEUNYING KALER SUBDISTRICT AT BANDUNG MUNICIPALITY INDONESIA - Sunasih Mulianingsih; Engkus; Tika Ayu Tri Lestari (Bajang Institute, 2021)
The quality of E-KTP service is one of the basic forms of government services to the community. The main problem of this research is that the quality of E-KTP service at the Cibeunying District Office, Bandung City is not optimal and not satisfactory. Optimizing e-KTP services is needed to improve service quality and satisfy the community. This synthesis is the subject of this article. The research method used is a qualitative approach with data collection techniques: observation, interviews and literature study. Based on the research results, the service is not optimal because it is not fully based on the dimensions: 1. Service Speed, 2. Cleanliness, Tidiness and Facilities; 3. Friendliness and Patience of Employees in Serving the speed of service; 4. Employees who are helpful and friendly and considerate of customers; 5. Security and Comfort.